2008
DOI: 10.25011/cim.v31i3.3468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adrenomedullin on the cell numbers and apoptosis of endothelial progenitor cells

Abstract: Clin Invest Med 2008; 31 (3): E117-E122. AbstractPurpose: To investigate the effect of adrenomedullin on the cell numbers and apoptosis of endothelial progenitor cells (EPCs). Methods: Mononuclear cells were isolated from peripheral blood by Ficoll density gradient centrifugation. The cells were stimulated with adrenomedullin, before and after the treatment of adrenomedullin-receptor antagonist, adrenomedullin 22-52, or a PI3K inhibitor LY294002. Results: Adrenomedullin dose-dependently increased the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Moreover, the protective effect of ADM on LPS-induced damage of Leydig cells was relatively the strongest when ADM was at the concentration of 100 nM. Data from the present study agree with those from previous reports [ 9 , 36 ], although the latter works involved other cell types, such as osteoblasts and endothelial progenitor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the protective effect of ADM on LPS-induced damage of Leydig cells was relatively the strongest when ADM was at the concentration of 100 nM. Data from the present study agree with those from previous reports [ 9 , 36 ], although the latter works involved other cell types, such as osteoblasts and endothelial progenitor cells.…”
Section: Discussionsupporting
confidence: 92%
“…itor and stem cells. These studies have shown that AM suppresses apoptosis and increases the number of early EPCs (23,29). In the present study, we show that these findings also apply to the highly proliferative late EPCs.…”
Section: Resultssupporting
confidence: 75%
“…This pathway regulates several important steps in angiogenesis including endothelial cell proliferation, migration, and capillary formation. PI3K/Akt also seem to mediate the antiapoptotic actions of AM on early EPCs (29). While prior studies have demonstrated that AM also induces endothelial cell proliferation and angiogenesis through the activation of MAPK, this was, however, not evident in the EPCs in our study using the MEK1/2 inhibitor U0126 (26).…”
Section: Resultsmentioning
confidence: 85%
“…It has been reported that ADM is not only able to enhance cell proliferation and angiogenesis ( 15 17 ), but can inhibit cell apoptosis ( 18 ). Furthermore, it has been demonstrated that ADM protects numerous cell types, including cardiomyocytes ( 19 ), rat Leydig cells ( 20 ), endothelial progenitor cells ( 21 ) and vascular endothelial cells ( 22 ), against apoptosis via the protein kinase B (Akt)/glycogen synthase kinase (GSK)3β signaling pathway. Akt is a powerful survival signal, which suppresses apoptosis and increases cell survival.…”
Section: Introductionmentioning
confidence: 99%